Cabbage, Swamp—Sabal palmetto (Walt.) Lodd ex Schult. & Schult.f. - James M. Stephens (EDIS)
This document details the cabbage palm (Sabal palmetto), Florida's state tree, known for its edible heart called swamp cabbage. The cabbage palm grows wild and is valued for landscaping. The document describes the plant's characteristics, harvesting methods, and traditional preparation techniques. It emphasizes the need for authorization before cutting the tree due to its protected status. The cabbage palm's central core is used in various dishes, including hearts of palm salad. Original publication date May 1994.